Triheptanoin improves brain energy metabolism in patients with Huntington disease. (3rd February 2015) - Adanyeguh, Isaac Mawusi; Rinaldi, Daisy; Henry, Pierre-Gilles; Caillet, Samantha; Valabregue, Romain; Durr, Alexandra; Mochel, Fanny
Abstract : Objective: Based on our previous work in Huntington disease (HD) showing improved energy metabolism in muscle by providing substrates to the Krebs cycle, we wished to obtain a proof-of-concept of the therapeutic benefit of triheptanoin using a functional biomarker of brain energy metabolism validated in HD. Methods: We performed an open-label study using 31 P brain magnetic resonance spectroscopy (MRS) to measure the levels of phosphocreatine (PCr) and inorganic phosphate (Pi) before (rest), during (activation), and after (recovery) a visual stimulus. We performed 31 P brain MRS in 10 patients at an early stage of HD and 13 controls. Patients with HD were then treated for 1 month with triheptanoin after which they returned for follow-up including 31 P brain MRS scan. Results: At baseline, we confirmed an increase in Pi/PCr ratio during brain activation in controls—reflecting increased adenosine triphosphate synthesis—followed by a return to baseline levels during recovery ( p = 0.013). In patients with HD, we validated the existence of an abnormal brain energy profile as previously reported. After 1 month, this profile remained abnormal in patients with HD who did not receive treatment. Conversely, the MRS profile was improved in patients with HD treated with triheptanoin for 1 month with the restoration of an increased Pi/PCr ratio during visual stimulation ( p = 0.005). Conclusion: This study suggests that triheptanoin is able to correct the bioenergetic profile in the brain of patients with HD at an early stage of the disease. Classification of evidence: This study provides Class III evidence that, for patients with HD, treatment with triheptanoin for 1 month restores an increased MRS Pi/PCr ratio during visual stimulation.